O estatuto do idealismo na fenomenologia de Husserl - Fontana, Vanessa Furtado (2007)
The goal of this dissertation is reflect on the concepts that validate the reasoning of transcendental idealism in the work of Husserl Ideas for a phenomenology pure and phenomenological philosophy. This work does not represent a radical change from part of the philosopher as portraying the commentators, but the apex of idealistic conception of science transcendental. The term idealism accumulates meanings expressed in many different currents of modern philosophy, which are all suspended by reducing philosophical in favor of a transcendental idealism inaugurate responsible for the problem of contemporary philosophy. The focus of the research is to think about the relevance of this idealism through the conceptual framework that surrounds the work cited. Among the topics investigated are the essences of intuition as intuition semantics of the transcendental experience. The intent as entrelaÃ§amento needed between subjectivity and objectivity, which represents the overcoming of any dichotomy. What I like pure subjectivity and dissolution of the opening of the semantic field of possibility. And the formation of transcendental spheres of the world under the transcendental pure possibility of sense. These concepts show the importance of understanding the phenomenology as transcendental idealism. A phenomenological science there is as transcendental idealism or semantic, incorporating the issues ontolÃ³gicas through descriptive analysis of the essences of donor direction to the plane factual